Indications for and results of axillary arterio-venous fistula in patients with a functionally single ventricle after cavopulmonary anastomosis. (5th January 2018) - Yurlov, Ivan A; Podzolkov, Vladimir P; Kovalev, Dmitry V; Chugueva, Irina A; Zelenikin, Mikhail M; Samsonov, Victor B; Chikin, Nikolay S; Yurpol'skaya, Lyudmila A; Mataeva, Tatyana V
Abstract: OBJECTIVES: This study aimed to investigate the indications for and the results of axillary arterio-venous fistula in patients with a functionally single ventricle at mid-term follow-up after bidirectional cavopulmonary connection. METHODS: From 2012 to 2017, 20 patients aged 21.1 ± 8.7 years (median 20.5) underwent axillary arterio-venous fistula after bidirectional cavopulmonary connection in our institution. The interval between bidirectional cavopulmonary connection and axillary arterio-venous fistula was 13.9 ± 7.2 years. The clinical and haemodynamic parameters of the patients were assessed before and after surgery. RESULTS: There was no in-hospital mortality. Paraesthesia of the arm persisted for 1–7 days. The mean arterial oxygen saturation increased from 72.4 ± 7.1% pre-surgery to 81.6 ± 5.5% ( P < 0.001) after surgery, and was 83.8 ± 6.5% at discharge ( P = 0.002 Wilcoxon matched pairs test). The haemoglobin, haematocrit, McGoon index and ejection fraction values did not change significantly. The speed and minute volume of the blood flow in the superior vena cava increased from from 21.1 ± 8.3 cm/s to 28.8 ± 14.9 cm/s ( P < 0.001) and from 10.6 ± 3.7 ml/s to 12.5 ± 2.9 ml/s ( P < 0.001), respectively. At the mid-term follow-up (1–5 years), 2 patients died from concomitant pathology. Stable improvement in the state and tolerance of physical activity was noted: before surgery, 17 patients were classified as New York Heart Association functional capacity (FC) III and 3 patients as FC IV; after surgery, 9 patients were FC II and 3 patients were FC III. One patient underwent a Fontan operation within 3 years. CONCLUSIONS: Axillary arterio-venous fistula can be used as the stage of surgical treatment and a bridge to Fontan and/or heart transplantation for this category of patients.